The Effect of Financial Inclusion, Literacy and Fintech on Small Business Profitability with Financial Behavior as an Intervening Variable and Financial Quotient as Moderating Variable in Ponorogo - Ervina, Ervina; Ratnawati, Tri; Brahmayanti, Ida Ayu Sri (PT Inovasi Pratama Internasional, 2024)
This research is focused on small businesses, as the growth of small businesses is a source of economic income in the Ponorogo City sub-district. The sales profit generated by small businesses each month is still relatively small and often decreases. These conditions reflect that the ability to generate profits in small businesses has not shown an increase in sales profit. This study aims to analyze the effect of financial inclusion, financial literacy, and fintech on small business profitability, with financial behavior as an intervening variable and financial quotient as a moderating variable, in the Ponorogo City District. The study sample consisted of 112 small businesses in the Ponorogo City District. The study employed the Smart Partial Least Square (PLS) method with an outer model and inner model test analysis. The results of this study indicate that financial inclusion has a significant effect on profitability, financial inclusion has a significant effect on financial behavior, financial literacy has a significant effect on profitability, financial literacy has no significant effect on financial behavior, fintech has no significant effect on profitability, fintech has a significant effect on financial behavior, financial behavior has a significant effect on profitability, and financial quotient cannot moderate the effect of financial inclusion on profitability. The moderating effect of financial quotient on the relationship between financial inclusion and financial behavior, financial inclusion and profitability, financial literacy and financial behavior, financial literacy and profitability, and fintech and profitability was not significant.